Hepatoprotective activity of raspberry ketone against streptozotocin-induced type 2 diabetes in male rats - Dalia Fouad; Doaa M. Elnagar; Ghaida Eid; Esraa Shuker (PLoS ONE, 2025)
Type 1 diabetes encompasses a spectrum of metabolic disorders marked by insulin deficiency, resulting in elevated blood glucose levels, commonly referred to as hyperglycemia. This persistent condition often precipitates lipid profile abnormalities, causing cholesterol alterations, low-and high-density lipoproteins, and triglycerides. The liver is particularly vulnerable to increased oxidative stress and inflammatory responses, which activate the transcription of pro-apoptotic genes and ultimately contribute to hepatocyte damage. This study analyzed the potential therapeutic role of raspberry ketone (RK), a natural antioxidant with antiapoptotic and anti-inflammatory properties, in male albino rats with induced type 2 diabetes. Fifty rats were equally divided into five groups: control, rats orally administered 200 mg /kg Body Weight (BW) RK for 5 days, diabetic rats intramuscularly injected once with 60 mg/kg BW streptozotocin, streptozotocin-induced diabetic rats orally administered 200 mg/kg BW RK for 5 days, and streptozotocin-induced diabetic rats orally administered 100 mg/kg metformin. Streptozotocin treatment significantly affected blood biochemical parameters, lipid profiles, oxidative stress markers, immunotoxicity biomarkers, and DNA damage biomarkers. Conversely, RK efficiently ameliorated the toxic effects of streptozotocin on the liver by reducing the pathological and biochemical changes associated with diabetes through its antioxidant and anti-inflammatory properties. Therefore, incorporating RK into the diet of diabetic patients can help prevent hepatocyte damage associated with diabetes. In conclusion, oral administration of RK exerts hepatoprotective effects by offering antioxidant, antiapoptotic, and anti-inflammatory properties against streptozotocin-induced type 1 diabetes in male rats.